Effectiveness of light emitting diode versus conventional phototherapy in neonatal hyperbilirubinemia: a hospital based observational study - Purkait, Radheshyam; Mondal, Manik (International Journal of Research in Medical Sciences, 2020)
Background: The most commonly used light sources in the conventional phototherapy units are compact fluorescent lamp (CFL), halogen spotlights and fiberoptic blankets. Recently light emitting diodes (LED) has emerged as better light source for phototherapy and almost replacing all the available conventional light sources. Comparative studies on the efficacy of LED versus conventional phototherapy are limited from India. That is why; this study was undertaken. Methods: 48 neonates of ≥35 weeks gestational age with hyperbilirubinemia were participated in this study. Among them, 24 neonates received conventional phototherapy and rest of them received LED phototherapy. The rate of fall of bilirubin levels at 6 hours and at completion along with total duration of phototherapy in both groups was measured. Results analysed by standard statistical methods. Results: LED phototherapy units showed higher rate of fall in bilirubin at six hrs (LED group: 0.38±0.05 mg/dl/hr versus conventional group: 0.30±0.04 mg/dl/hr, p<0.05) and after completion of therapy (LED group: 0.32±0.03 mg/dl/hr versus conventional group: 0.26±0.03 mg/dl/hr, p<0.05) compared to conventional group. Significant difference was documented in total duration of phototherapy in LED group (30.8±1.8 hours) when compared to conventional group (34.6±0.7 hours). None of the neonate showed phototherapy failure. Side effects were minimal and comparable in both the groups. Conclusions: The LED phototherapy units are more efficacious in terms of higher rate of fall of bilirubin levels and lesser duration of phototherapy compared to conventional phototherapy units.